Virtual Learning Improves Attendance for Critical Care Education During the COVID-19 Pandemic - Scioscia, Andrea; Rakkar, Jaskaran; Pelletier, Jonathan H.; Ghassemzadeh, Rod; Hamilton, Melinda F.; Fuhrman, Dana Y. (Journal of Pediatric Intensive Care, 2021)
The COVID-19 pandemic has pushed medical educators and learners to adapt to virtual learning (VL) in an expedited manner. The effect of VL for critical care education has not yet been evaluated. In a quantitative analysis of survey data and attendance records, we sought to determine the association of VL with conference attendance and work-life balance. Attending physicians, fellows, and advanced practice providers (APP) at a pediatric critical care department at a quaternary children's hospital participated in the study. Attendance records were obtained before and after the adaption of a VL platform. In addition, an electronic, anonymous survey to evaluate current satisfaction and the strengths and weaknesses of VL as well as its impact on work-life balance was administered. In total, 31 learners (17 attending physicians, 13 fellows, and 1 APP) completed the survey. A total of 83.9% (26/31) of participants were satisfied, and 77.4% (24/31) found VL to be similar or more engaging than non-VL. However, 6.5% (2/31) of learners reported difficulty in using the new platform, 87% (27/31) of participants supported VL as an effective learning tool, and 83.3% (25/30) reported a positive impact on work-life balance. Additionally, median monthly conference attendance increased significantly from 85 to 114 attendees per month (p < 0.05). Our results suggest that a virtual model has advantages for overall attendance and work-life balance. We anticipate VL will continue to be an integral part of medical education. Future work evaluating the impact of VL on interdepartmental and interinstitutional collaborations is needed.
Keywords: pediatric; learning; education; medical education; pandemics